TOM NESMITH, GREG BAK, and JOAN SCHWARTZ, eds., All Shook Up: The Archival Legacy of Terry Cook - Waiser, Bill (Archivaria, 2020)
All Shook Up: The Archival Legacy of Terry Cook. Tom Nesmith, Greg Bak, and Joan Schwartz, eds. Chicago: Society of American Archivists, 2020. ISBN 978-1-945246-31-9; 978-1-945246-30-2